Β-lactam and β-lactamase inhibitor combinations in the treatment of extended-spectrum β-lactamase producing Enterobacteriaceae: time for a reappraisal in the era of few antibiotic options?. Issue 4 (April 2015) - Harris, Patrick N A; Tambyah, Paul A; Paterson, David L
Summary The spread of extended-spectrum β-lactamase (ESBL) genes in Enterobacteriaceae such as Escherichia coli or Klebsiella spp is a major challenge to modern medical practice. Carbapenems are the treatment of choice for serious infections caused by ESBL producers; however, carbapenem resistance has increased globally. ESBL producers might be susceptible to β-lactam-β-lactamase inhibitor (BLBLI) combination antibiotics such piperacillin–tazobactam or amoxicillin–clavulanate. These drugs are frequently avoided in serious infections caused by ESBL producers because of the inoculum effect in-vitro (especially for piperacillin–tazobactam), animal data suggesting inferior efficacy when compared with carbapenems, concerns about pharmacokinetic–pharmacodynamic drug target attainment with standard doses, and poor outcomes shown in some observational studies. Prospective cohort data and a meta-analysis suggest that BLBLIs are non-inferior to carbapenems in the treatment of bloodstream infections caused by ESBL producers. We examine why BLBLIs are perceived as inferior in the treatment of infection with ESBL producers, and discuss data that suggest these concerns might not be strongly supported by clinical evidence.